Modelo de gestión administrativa para centros de acopio de productos agrícolas en el cantón Bolívar - Bazurto Párraga, Luis Cayetano (2022)
The main objective of the research was the development of an administrative management model for the collection centers of agricultural products in Bolívar canton as a contribution to the improvement of their competitiveness. To fulfill this objective, a previously established procedure was proposed, made up of three phases that led to the pursuit of the specific objectives; the first objective corresponding to the diagnosis of the current situation of the agricultural product collection centers in Bolívar canton, to determine a real scenario in the administrative management process; In the second objective, the behavior of the supply chain was analyzed for the establishment of the administrative management functions of the collection centers. The third objective consisted of structuring the elements that make up the administrative management model with the identification of the corresponding phases for its implementation in collection centers for agricultural products. A set of techniques and tools such as the interview, survey and the observation sheet were applied to collect important data for the study. The applied methods were analytical, synthetic, quantitative-deductive and statistical, additional, for the structuring of indicators it was necessary to develop the Delphi method. Having as the main result that the form of organizational management is empirical since it does not have a defined structure, which means that the processes carried out do not have a technification. The conclusions and recommendations obtained from the research work carried out are presented.